PERCEPTIONS AND READINESS OF THE HEALTH POLYTECHNIC OF THE MINISTRY OF HEALTH RIAU STUDENTS IN IMPLEMENTING IPE-BASED OF INTEGRATED REAL WORK PRACTICE - Dewi Erowati; Yolahumaroh Yolahumaroh; Alkausyari Aziz (Poltekkes Kemenkes Bengkulu, 2022)
Interprofessional Education (IPE) emphasizes collaborative practice between two or more health professions. The Integrated Real Work Practice of the Health Polytechnic of the Ministry of Health Riau applies the IPE concept, among students of nutrition, midwifery, and nursing. Core competencies for IPE are roles and responsibilities; ethical practice; conflict resolution; communication; and collaboration and teamwork. The purpose of this study was to analyze the relationship between students' perceptions and readiness in implementing the IPE-based of integrated real work practice of the Health Polytechnic of the Ministry of Health Riau. This research is a descriptive study using a cross sectional design in which the measurement of variables was only done once at a time. The sample collection technique was accidental sampling of final year students who attended the integrated real work practice of the Health Polytechnic of the Ministry of Health Riau. The total sample of the study was 230 students, consisting of 76 nutrition students, 63 midwifery students, and 91 nursing students. The instruments used in this study were the Interdisciplinary Education Perception Scale (IEPS) to measure student perceptions and the Readiness for Interprofessional learning Scale (RIPLS) to measure student readiness. The data was carried out in May 2022 and then been analyzed using the Chi Square method to mesure the relationship between the perception and the readiness of the students. The results showed that there was a statistically significant relationship (p = 0.000 or p <0.05) between perceptions and readiness of the Health Polytechnic of the Ministry of Health Riau students in the implementation of IPE-based integrated real work practice. IPE can be implemented successfully and benefits students in real community problems. The program should be evaluated and improved to assure all students from different schools to get equal benefits.